Interactive Media Using Articulate Storyline 3 for Fifth Grade Elementary Students to Enhance Speaking Skills - I Gede Agus Sudiantara; I Wayan Widiana; I Made Suarjana (Journal of Education Technology, 2024)
This research addresses students' low speaking skills and the underutilization of learning media in educational activities. The objectives of this study include the development of a prototype of interactive media based on audiovisual using articulate storyline 3, analysis of the validity of the media content, students' responses to the media, and analysis of its effectiveness on the speaking skills of fifth grade elementary school students. This study adopts the ADDIE model with the subject of interactive media based on audiovisual articulate storyline 3, and the objects of research include the validity of the media content, material content, user responses, and the effectiveness of the media. Data collection methods involve interviews, observations, and questionnaires with observation guideline instruments, rating scale sheets, interview guidelines, and questionnaires. The data that has been collected will be tested using the Kolmogorov-Smirnov and Shapiro-Wilk tests. Furthermore, the homogeneity of variance test and t-test are carried out. The availability of this interactive learning media innovation based on audiovisual articulate storyline 3 can facilitate students in supporting the learning process and help teachers achieve better learning goals. The results of the study indicate that the interactive media produced has a high level of content validity, the interactive media material obtains high content validity, the students' response to the media is very good. This media is significantly effective in improving the speaking skills of fifth grade elementary school students. This study has implications for the optimal use of technology in the field of education to support students' skills.